ANALISIS KEMAMPUAN LITERASI DIGITAL ORANG TUA DAN PENGARUHNYA TERHADAP PENGGUNAAN INTERNET PADA ANAK USIA DINI DAN REMAJA - Intan Purnama Dewi; Daddy Darmawan; Henny Herawaty Br. Dalimunthe (Universitas Negeri Jakarta, 2024)
This study aims to analyze the influence of parental digital literacy on internet use in early childhood and adolescence in Bulak Village. The method used is Structural Equation Modeling (SEM) to test the relationship between latent variables of parental digital literacy and children's internet use. Data were obtained from 40 respondents using a questionnaire consisting of digital literacy indicators, such as functional skills and beyond, critical thinking and evaluation, and internet use indicators, such as internet access habits and time efficiency. The results showed that the digital literacy skills of parents in Bulak Village were at a moderate to high level, with the leading indicators being 1) functional skills and beyond, 2) creativity, 3) collaboration, 4) communication, 5) The ability to find and select information; 6) critical thinking and evaluation; 7) cultural and social understanding; 8) e-safety. Path analysis showed that parental digital literacy had a positive and significant influence on children's internet use (γ=0.72) (p <0.05). Parental digital literacy significantly shapes safe and productive internet usage patterns for their children. Parents with good digital literacy can guide their children in using the internet for educational and entertainment purposes. Therefore, digital literacy training for parents and digital safety campaigns are highly recommended to maximize the positive impact of internet use on young children and adolescents.